2020
DOI: 10.1161/hypertensionaha.120.15295
|View full text |Cite
|
Sign up to set email alerts
|

Renal Perfusion Pressure Determines Infiltration of Leukocytes in the Kidney of Rats With Angiotensin II–Induced Hypertension

Abstract: The present study examined the extent to which leukocyte infiltration into the kidneys in Ang II (angiotensin II)-induced hypertension is determined by elevation of renal perfusion pressure (RPP). Male Sprague-Dawley rats were instrumented with carotid and femoral arterial catheters for continuous monitoring of blood pressure and a femoral venous catheter for infusion. An inflatable aortic occluder cuff placed between the renal arteries with computer-driven servo-controller maintained RPP to the left kidney at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…We have recently reported, by servocontrolling renal perfusion pressure (RPP), that the chronic elevation of RPP drives the infiltration of inflammatory cells into the kidneys in 2 models of hypertension, Dahl salt-sensitive (SS) rats fed a high-salt diet 2 and Sprague-Dawley (SD) rats infused with angiotensin II. 3 We further showed that T-cell deficiency attenuates but does not eliminate the development of salt-sensitivity 4 and angiotensin II-mediated hypertension. 5 Similarly, CCL2 (C-C motif chemokine ligand 2) inhibition 6 has been found to attenuate salt-sensitive hypertension but only after the initial rise of blood pressure is clearly established, consistent with the leukocyte infiltration being secondary to hypertension.…”
mentioning
confidence: 81%
“…We have recently reported, by servocontrolling renal perfusion pressure (RPP), that the chronic elevation of RPP drives the infiltration of inflammatory cells into the kidneys in 2 models of hypertension, Dahl salt-sensitive (SS) rats fed a high-salt diet 2 and Sprague-Dawley (SD) rats infused with angiotensin II. 3 We further showed that T-cell deficiency attenuates but does not eliminate the development of salt-sensitivity 4 and angiotensin II-mediated hypertension. 5 Similarly, CCL2 (C-C motif chemokine ligand 2) inhibition 6 has been found to attenuate salt-sensitive hypertension but only after the initial rise of blood pressure is clearly established, consistent with the leukocyte infiltration being secondary to hypertension.…”
mentioning
confidence: 81%
“…We hypothesize (Figure 1), 6,7 based upon data from Dahl SS and angiotensin II-hypertensive rats, 51,52,53 that an initial increase in blood pressure is transmitted to the renal vasculature and mediates the infiltration of immune cells into the kidney. The mechanism is unclear, but it is possible that the elevated perfusion pressure results in tissue damage and triggers the migration of innate and adaptive immune cells into the kidney.…”
Section: Mechanisms Of Immune Activation In Salt-sensitive Hypertensionmentioning
confidence: 99%
“…There is increasing evidence to show that peritubular capillaries play an important role in CKD and are a key regulator of CKD progression [39]. Peritubular capillary rarefaction is found not only in diabetic nephropathy [40] and hypertensive nephropathy [41], but also in IgA nephropathy [42], congenital nephrotic syndrome [43], lupus nephritis [44], and polycystic kidney disease [45]. Thus, protecting peritubular capillaries is a crucial approach to alleviating renal brosis [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%